Oral Delivery of Biologics in Inflammatory Bowel Disease Treatment - Zhang, Wunan; Michalowski, Cecilia Bohns; Beloqui, Ana (Frontiers in Bioengineering and Biotechnology, 2021)
Inflammatory bowel disease (IBD) has been posed as a great worldwide health threat. Having an onset during early adulthood, IBD is a chronic inflammation disease characterized by remission and relapse. Due to its enigmatic etiology, no cure has been developed at the moment. Conventionally, steroids, 5- aminosalicylic acid and immunosuppressants have been applied clinically to relieve patients’ syndrome which, unfavorably, cause severe adverse drug reaction including diarrhea, anemia and glaucoma. Insufficient therapeutic effects also loom and surgical resection is mandatory in half of the patients within 10 years after diagnosis. Biologics demonstrated unique and differentiative therapeutic mechanism which can alleviate the inflammation more effectively. However, their application in IBD has been hindered considering their stability and toxicity. Scientists have brought up with the concept of nanomedicine to achieve the targeted drug delivery of biologics for IBD. Here, we provide an overview of biologics for IBD treatment and we review existing formulation strategies for different biologic categories including antibodies, gene therapy and peptides. This review highlights the current trends in oral delivery of biologics with an emphasis on the important role of nanomedicine in development of reliable methods for biologic delivery in IBD treatment.